Efficiency of global airlines: An application of the metafrontier dea model - Abdullah, Muhammad Asraf; Satar, Nurulhuda Mohd (Universiti Malaysia Sarawak, 2019)
This paper evaluates the technical efficiency of low cost and full cost carriers over the period 2002 to 2011 amid the high level of competition faced by airlines in Asia and Europe since the 2000s using the metafrontier technique based on Data Envelopment Analysis methodology. The application of this technique to airlines is interesting in order to identify the technology gap between low cost and full cost carriers. The study findings suggest that full cost carriers are technically more efficient than their low cost counterparts. The high value of TGR between the full cost carrier group and the metafrontier technical efficiencies indicates that full cost carriers have achieved the highest potential output. © 2019, Universiti Malaysia Sarawak. All rights reserved.